Recovery of energy and iron from oily sludge pyrolysis in a fluidized bed reactor. (1st May 2015) - Qin, Linbo; Han, Jun; He, Xiang; Zhan, Yiqiu; Yu, Fei
Abstract: In the steel industry, about 0.86 ton of oily sludge is produced for every 1000 tons of rolling steel. Due to the adverse impact on human health and the environment, oily sludge is designated as a hazardous waste in the Resource Conservation and Recovery Act (RCRT). In this paper, the pyrolysis treatment of oily sludge is studied in a fluidized bed reactor at a temperature range of 400–600 °C. During oily sludge pyrolysis, a maximum oil yield of 59.2% and a minimum energy loss of 19.0% are achieved at 500 °C. The energy consumption of treating 1 kg oily sludge is only 2.4–2.9 MJ. At the same time, the energy of produced oil, gas and solid residue are 20.8, 6.32, and 0.83 MJ, respectively. In particular, it is found that the solid residue contains more than 42% iron oxide, which can be used as the raw material for iron production. Thus, the simultaneous recovery of energy and iron from oil sludge by pyrolysis is feasible. Graphical abstract: In the steel industry, about 0.86 ton of oily sludge is produced for every 1000 tons of rolling steel. Due to the adverse impact on human health and the environment, oily sludge is designated as a hazardous waste in the Resource Conservation and Recovery Act (RCRT). In this paper, the pyrolysis treatment of oily sludge is studied in a fluidized bed reactor at a temperature range of 400–600 °C. During oily sludge pyrolysis, a maximum oil yield of 59.2% and a minimum energy loss of 19.0% are achieved at 500 °C. The energy consumption of treating oily sludge is only 2.4–2.9 MJ/kg. At the same time, the energy of oil, gas and solid residue from 1 kg oily sludge are 20.8, 6.32, and 0.83 MJ, respectively. In particular, it is found that the solid residue contains more than 42% iron oxide, which can be used as the raw material for iron production. Thus, the simultaneous recovery of energy and iron from oil sludge by pyrolysis is feasible. Highlights: The hazardous oily sludge was safely disposed by pyrolysis. The energy and iron from the oil sludge were simultaneous recycled. The maximum oil yield (59.20%) was achieved at 500 °C during oily sludge pyrolysis. The solid residues after pyrolysis contained more than 42% iron oxide.